56=-2(21-m)+4(m-4)

Simple and best practice solution for 56=-2(21-m)+4(m-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 56=-2(21-m)+4(m-4) equation:


Simplifying
56 = -2(21 + -1m) + 4(m + -4)
56 = (21 * -2 + -1m * -2) + 4(m + -4)
56 = (-42 + 2m) + 4(m + -4)

Reorder the terms:
56 = -42 + 2m + 4(-4 + m)
56 = -42 + 2m + (-4 * 4 + m * 4)
56 = -42 + 2m + (-16 + 4m)

Reorder the terms:
56 = -42 + -16 + 2m + 4m

Combine like terms: -42 + -16 = -58
56 = -58 + 2m + 4m

Combine like terms: 2m + 4m = 6m
56 = -58 + 6m

Solving
56 = -58 + 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
56 + -6m = -58 + 6m + -6m

Combine like terms: 6m + -6m = 0
56 + -6m = -58 + 0
56 + -6m = -58

Add '-56' to each side of the equation.
56 + -56 + -6m = -58 + -56

Combine like terms: 56 + -56 = 0
0 + -6m = -58 + -56
-6m = -58 + -56

Combine like terms: -58 + -56 = -114
-6m = -114

Divide each side by '-6'.
m = 19

Simplifying
m = 19

See similar equations:

| -17=x-36 | | T=0.6(205-18/2-144)+144 | | 0.40=ln(y) | | 6(4x-7)-4=6(x-4)+104 | | 3x-2-5x=x+2+x | | 16p^4-4p^2=0 | | 6/5+2/5x=29/10+5/2x+1/2 | | 9x-8x=19fory | | 2(x-5)+10=-(-3x+2) | | 5(3x-7)-8=5(x-3)+22 | | 11y+15x=-23 | | 7x+n=5 | | 10=11x | | 5(-7x-5)-4x=2 | | (7c-5)(8c+4)= | | 2(10x-5)-9x=11x+13 | | 4+(10+10)+x=30 | | 5/18=-y/6 | | x+9.3=8 | | n+2=-14-4 | | -7/8t=1/4 | | 7k+2=4x-10 | | 1/5m=9/5 | | -7.6=u/4-1.2 | | 0.20(x+30)+0.20x=10 | | e^7x=3 | | 3/5x+5=7 | | 6/5=2x | | 0.20(x+30)+0.20x= | | x/3=x/4-3 | | (1/x-2)+(x/x+2)=(5/x^2-4) | | 8x+3/7+x-4/4=5 |

Equations solver categories